Mechanical properties of eco-friendly cements-based glass powder in aggressive medium. (2022) - Almeshal, Ibrahim; Al-Tayeb, Mustafa M.; Qaidi, Shaker M.A.; Abu Bakar, B.H.; Tayeh, Bassam A.
Abstract: Recycling glass waste for developing sustainable cementitious mortar and concrete have recently attracted increasing attentions for the construction industry. From another aspect, the nitrate-based environment due to chemical fertilizers has a significant effect on reinforced concrete and normal concrete by producing damages like its microstructure, corrosion of reinforcement. The major goal of this research work is to study the effect of Ammonium Nitrate (NH4 NO3 ) on the unite weight and strength of glass mortar by performing experimental tests. In this article, eco-friendly mortar containing recycled glass powder (GP), as a replacement to cement, is submerged in NH4 NO3 solutions. In total, 60 cement mortar mixtures were proportioned in this research work used GP passing sieves 200 µm. NH4 NO3 solutions with 5, 10, and 20% concentration, and three different exposure periods 10, 30, and 60 days were applied. The experimental results showed that the effect of NH4 NO3 on the density of mortar containing GP is less critical than that of conventional mortar. After 60 days of immersion in the solution with a concentration of 20% NH4 NO3, the reduction in density of glassy mortar is less than that of ordinary mortar. Furthermore, the results indicated that the maximum compressive strength was attained at 10% replacement level of cement with GP by approximately 60 MPa after 60 days of immersion in NH4 NO3 solution.